Spanish cinema of the new millennium : and the winner is-- - Deveny, Thomas G., 1950- (Intellect, 2019)
Spanish Cinema of the New Millennium provides a new approach to the study of contemporary Spanish cinema between 2000 and 2015, by analysing films that represent both 'high' and 'popular' culture side by side.